Anti-stigma campaign: the COVID-19 stigma and associated factors among Chinese young students - Wang, Cong; Mu, Yun-Fei; Cai, Jia; Wang, Yu; Deng, Zhong-Yue; Deng, Ai-Ping; Song, Hong-Jun; Zhang, Tian-Ming; Zhao, Xin-Yi; Yang, Yi-Yue; Yin, Li; Huang, Yi; et al. (Frontiers in Public Health, 2025)
IntroductionCOVID-19-related stigma, a persistent consequence of the pandemic, poses a significant threat to the well-being of individuals, particularly young students in crucial developmental stages. This study aimed to investigate the prevalence of stigma views towards COVID-19 patients among young students in Sichuan Province, China, following the lifting of pandemic restrictions, and explored the associated influencing factors.MethodsA cross-sectional survey was conducted online involving 82,873 young students. Data on demographic information, COVID-19-related experiences, and stigma views were collected. Logistic regression analysis identified risk factors for stigma, while Random Forest (RF) modeling ranked the importance of these factors.Results20,155 (24.3%) participants reported stigmatizing views toward COVID-19 patients. Higher levels of psychological stress, particularly post-restriction lifting, significant emerged as a risk factor for stigma. Both self-infection and family members' infection were risk factors of stigma, although psychological stress proved more influential. Furthermore, male students, those from minority groups, and those with rural household registrations exhibited higher stigma risk.DiscussionThese findings highlight the enduring nature of COVID-19 stigma among young students even after restrictions lifted. Targeted interventions aimed at reducing stigma and mitigating psychological stress are crucial for supporting the well-being of this vulnerable population.